2018
DOI: 10.1097/md.0000000000013771
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of thoracic paravertebral block for thoracoscopic surgery

Abstract: Background:The efficacy of thoracic paravertebral block for thoracoscopic surgery remains controversial. We conduct a systematic review and meta-analysis to explore the impact of thoracic paravertebral block on thoracoscopic surgery.Methods:We search PubMed, EMbase, Web of science, EBSCO, and Cochrane library databases through August 2018 for randomized controlled trials (RCTs) assessing the effect of thoracic paravertebral block on thoracoscopic surgery. This meta-analysis is performed using the random-effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 32 publications
2
17
0
1
Order By: Relevance
“…Pulmonary complications represent an important group of complications after radical resection for lung cancer and can prolong the hospital stay. One retrospective study showed that general anesthesia combined with TPVB may reduce postoperative pulmonary complications [18], and other studies have shown that TPVB can shorten the postoperative hospital stay [19,20]. Our study showed that there was no difference in postoperative pulmonary complications or hospital stay between the two groups.…”
Section: Discussionsupporting
confidence: 51%
“…Pulmonary complications represent an important group of complications after radical resection for lung cancer and can prolong the hospital stay. One retrospective study showed that general anesthesia combined with TPVB may reduce postoperative pulmonary complications [18], and other studies have shown that TPVB can shorten the postoperative hospital stay [19,20]. Our study showed that there was no difference in postoperative pulmonary complications or hospital stay between the two groups.…”
Section: Discussionsupporting
confidence: 51%
“… 26 The meta-analysis of Hu et al showed that the analgesic effect of TPVB after thoracotomy was lower than that of non-paravertebral block, with fewer side effects. 27 However, Hu et al did not compare TPVB with TEA, and it was unclear which analgesic method was more suitable for thoracotomy. Baidya et al conducted a meta-analysis of postoperative scores for resting and coughing pain at 4–8 hours and found that TEA and TPVB showed similar analgesic effects after thoracotomy.…”
Section: Discussionmentioning
confidence: 99%
“…One of the first publications on paravertebral block (PVB) including a 2 year follow-up period was the 1998 report of Coveney and colleagues (39) in patients with breast cancer surgery. Since then, PVB has been used for pain control in different surgical settings, mainly after thoracic surgery (40). Norum and Breivik (41) do not consider PVB equivalent to EDA in thoracic surgery.…”
Section: Neuraxial Blocks-paravertebral Cathetersmentioning
confidence: 99%